“One Day on the Red Hills of Georgia”: The Effects of Immigration Status on Latino Migrants’ Experience of Discrimination, Utilization of Public Services, and Attitudes toward Acculturation - Mikhail Lyubansky; Paul A. Harris; William E. Baker; Cameron D. Lippard (Norteamérica)
This study documents the experiences and identities of undocumented Spanish-speaking migrants in Georgia vis-à-vis their counterparts who have legal status. Structured interviews were used to collect data from 127 adults (49 percent undocumented at their time of arrival and 38 percent undocumented at the time of data collection) regarding their experience of discrimination, utilization of services, identity preferences, mental health, and beliefs in five domains: vulnerability, injustice, distrust, superiority, and helplessness. Significant immigration status differences emerged for education, income, utilization of some city services, and a few of the belief scales. However, the documented and undocumented samples were more similar than different.